2020
DOI: 10.4269/ajtmh.20-0830
|View full text |Cite
|
Sign up to set email alerts
|

Sanitation Practices during Early Phases of COVID-19 Lockdown in Peri-Urban Communities in Tamil Nadu, India

Abstract: In countries without adequate access to improved sanitation, government-imposed restrictions during the COVID-19 pandemic can impact toilet usage. In India, where millions have recently transitioned to using a toilet, pandemic-related barriers to use might increase open defecation practices. We assessed changes in reported defecation practices in peri-urban communities in Tamil Nadu. Field assistants conducted phone surveys in 26 communities in two districts from May 20, 2020 to May 25, 2020. They asked respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 28 publications
2
21
0
Order By: Relevance
“…Our results related to handwashing as a COVID-19 preventative measure are generally in agreement with other studies. There were high levels of reported handwashing as a preventative measure in online surveys throughout India; [22][23][24][25][26] in a phone survey in Tamil Nadu, India; 27 and in in-person surveys in Ethiopia 28 and Kenya, 29 all of which found at least 85% of respondents reported handwashing to prevent COVID-19. However, many of these surveys did not specify water source access, the use of soap, or if there was a change in handwashing practices.…”
Section: Discussionmentioning
confidence: 99%
“…Our results related to handwashing as a COVID-19 preventative measure are generally in agreement with other studies. There were high levels of reported handwashing as a preventative measure in online surveys throughout India; [22][23][24][25][26] in a phone survey in Tamil Nadu, India; 27 and in in-person surveys in Ethiopia 28 and Kenya, 29 all of which found at least 85% of respondents reported handwashing to prevent COVID-19. However, many of these surveys did not specify water source access, the use of soap, or if there was a change in handwashing practices.…”
Section: Discussionmentioning
confidence: 99%
“…The research points also to a big urban-rural divide and thus to the importance of socio-economic factors when it comes to compliance. In fact, several barriers to NPIs have been reported in peri-urban and rural areas in India [202] , [203] , [214] . Individuals living in urban settings report a better knowledge about COVID-19 and better opportunities to adopt hygienic behaviors.…”
Section: Surveysmentioning
confidence: 99%
“…This is in line with the results of another study in Tamil Nadu, India, which also found minimal change in defecation practices with 92% of respondents reporting no change since the lockdown and the majority of respondents with a private latrine continuing to use it and only a few (7%) beginning to use their private latrine as a result of the pandemic. 27 Our study area had high levels of latrine coverage and use prior to the pandemic, 30 which may have also contributed to the minimal change observed. Our qualitative findings also suggest little change in the decision-making or motivational factors individuals typically consider when choosing their place of defecation.…”
Section: Discussionmentioning
confidence: 87%
“…34 We found in our study that good WASH infrastructure enabled compliance with preventive measures like handwashing or staying home, as participants were able to use their latrine and wash their hands at home. A separate study in Tamil Nadu, India found that respondents of the same age, gender, and education who had access to a private toilet were more likely to report they increased the frequency of handwashing since the lockdown, 27 further suggesting that infrastructure played a role in COVID-19 handwashing practices. Overall, these findings suggest that investments in WASH infrastructure, such as a piped water supply, not only ensure individuals have an enabling environment to perform promoted WASH practices but may also play a role in building the resilience of rural communities against future disease outbreaks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation